Question #12803

2 Answers
Dec 12, 2017

5x^2+8x-6

Explanation:

"assuming you mean to simplify"

4x^2+5x+x^2+3x-6

"we simplify the expression by "color(blue)"collecting like terms"

"like terms are terms which contain the same variable (letter)"

"note that "x^2=x xx x

"and is different to a term only containing x"

rArrcolor(red)(4x^2)color(blue)(+5x)color(red)(+x^2)color(blue)(+3x)-6

"to collect like terms we add the "color(magenta)"coefficients"
"of the numbers in front of the variables"

=(color(red)(4x^2+1x^2))+(color(blue)(5x+3x))-6

=color(red)(5x^2)color(blue)(+8x)-6

Dec 12, 2017

You mean: 4x^2+5x+x^2+3x-6

Explanation:

5x^2+8x-6

Since I don't know what to do with it.... I guess:

  1. 5x^2+8x-6=0

x_(1,2)=(-b+-sqrt(b^2-4ac))/(2a)

x_(1,2)=(-8+-sqrt(64-4*5*(-6)))/(2*5)=(-8+-sqrt(64+120))/(2*5)

x_(1,2)=(-8+-sqrt(184))/(2*5)=(-4*cancel2+-cancel2sqrt(46))/(cancel2*5)

x_(1,2)=(-4+-sqrt(46))/(5)

[x-((-4-sqrt(46))/5)]*[x-((-4+sqrt(46))/5)]=0